2008
DOI: 10.2215/cjn.03220807
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Alcohol Ingestions

Abstract: Alcohol-related intoxications, including methanol, ethylene glycol, diethylene glycol, and propylene glycol, and alcoholic ketoacidosis can present with a high anion gap metabolic acidosis and increased serum osmolal gap, whereas isopropanol intoxication presents with hyperosmolality alone. The effects of these substances, except for isopropanol and possibly alcoholic ketoacidosis, are due to their metabolites, which can cause metabolic acidosis and cellular dysfunction. Accumulation of the alcohols in the blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
347
0
46

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(398 citation statements)
references
References 120 publications
(319 reference statements)
5
347
0
46
Order By: Relevance
“…Physicochemically, it is similar to ethylene glycol but less toxic [48]. PG toxicity is typically characterized by acidosis, increased AG and/or OG, hypernatremia, or hepatic dysfunction, with increase in direct serum bilirubin and acute kidney injury [49].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Physicochemically, it is similar to ethylene glycol but less toxic [48]. PG toxicity is typically characterized by acidosis, increased AG and/or OG, hypernatremia, or hepatic dysfunction, with increase in direct serum bilirubin and acute kidney injury [49].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Study of antioxidant activity showed that methanol was the best organic solvent for pineapple extract [2,11]. However, methanol is a toxic organic solvent which caused several health problems [12]. Mixtures of ethanol and water are an environmentally preferable solvent [13].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma ketones and salicylates were not detected. A plasma osmolal gap (the difference between the measured and the estimated plasma osmolality) .20 mosmol/kg is a clue to the presence of an alcohol in the circulation (7). The estimated plasma osmolality was 296 mosmol/kg, and the measured plasma osmolality was 311 mosmol/kg.…”
Section: Discussionmentioning
confidence: 97%